Probiotics in the prevention and tratamento of periodontal diseases - Massambani, Natan Santos (2021)
Literature has shown that probiotics can be a possible ally in the prevention and treatment of periodontal diseases. The present study aims to review the literature regarding the use of probiotics in prevention and treatment of periodontal diseases. In most of the clinical studies included in this literature review, probiotics showed favorable results when used in prevention and as an adjunct to the treatment of gingivitis and periodontitis, bringing an improvement in the plaque index, gingival index and reduction in probing depth, in addition to the reduction of periodontopathogenic microorganisms and alteration of the immune response. Probiotics showed favorable results in most clinical studies included in this literature review, when used in prevention and as an adjunct. Further studies are still needed to establish clearer protocols regarding the most indicated strains, form of administration and time of use.